Low-cost capacitive CMOS capacitive E. Coli biosensor for point-of-need water quality monitoring - Joubert, Trudi-Heleen (University of Pretoria, 2023)
Dissertation (MEng (Microelectronic Engineering))--University of Pretoria, 2023.